2012
DOI: 10.1002/adem.201200180
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film Synthesis of Ti3SiC2 by Rapid Thermal Processing of Magnetron‐Sputtered TiCSi Multilayer Systems

Abstract: The ternary compound Ti 3 SiC 2 has a nanolaminated structure and belongs to the class of M nþ1 AX n phases. MAX phases have a high potential to be used as high temperature contacts on different substrates. They combine metallic and ceramic properties, like relative high electrical conductivity and high oxidation resistance, due to their nanolaminated structure. In the last 20 years there were several attempts to reduce the formation temperature of MAX phases by different sputtering techniques. Eklund et al. [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Emmerlich [19] obtained Ti 3 SiC 2 by reactive magnetron cosputtering from three elemental targets at 750 °C, however, with competitive TiC y growth. Most recently it was shown [21] that multilayer magnetron sputtered Ti-C-Si system deposited at room temperature onto silicon with native oxide can be annealed at 1000 °C in rapid thermal annealing system with 0 s holding time and converted into Ti 3 SiC 2 MAX phase.…”
mentioning
confidence: 99%
“…Emmerlich [19] obtained Ti 3 SiC 2 by reactive magnetron cosputtering from three elemental targets at 750 °C, however, with competitive TiC y growth. Most recently it was shown [21] that multilayer magnetron sputtered Ti-C-Si system deposited at room temperature onto silicon with native oxide can be annealed at 1000 °C in rapid thermal annealing system with 0 s holding time and converted into Ti 3 SiC 2 MAX phase.…”
mentioning
confidence: 99%
“…Another approach of thin film MAX phase synthesis is the multilayer synthesis approach depositing elemental multilayer by magnetron sputtering at room temperature and subsequent rapid thermal annealing as used in this work [20][21][22]. Furthermore, depositing of multilayer systems at elevated temperatures [23], and longer thermal processing [24,25] was applied.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their interesting property combination MAX phase materials are promising as surfaces in electrical sliding contacts or other tribological systems used in thermal or chemical aggressive environments. As the applied thin film syntheses are based on the deposition of elemental multilayers and subsequent annealing [20][21][22], also the sliding properties of the deposited multilayers were investigated to gain information about the influence of the annealing process and the formation of the MAX phases on the tribological properties. In this paper experimental results on the tribological behavior of the thin films against the counterpart material 1.3505 are presented.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, using dc magnetron sputtering from a compound target, Walter et al [8] have reported formation of single-phase Cr 2 AlC thin films on stainless steel substrates heated at temperatures around 650ºC. However it is clear that, from an industrial viewpoint, deposition at high temperatures is less attractive than deposition without additional heating (cold deposition) followed by annealing to promote crystallisation and true MAX phase state.Rapid thermal annealing has been successfully shown to create a MAX phase after deposition at low temperature [21]. One also needs to bear in mind that "cold" PVD while not achieving a nanolaminated atomic structure would create an almost amorphous bonding network.…”
mentioning
confidence: 99%
“…Rapid thermal annealing has been successfully shown to create a MAX phase after deposition at low temperature [21]. One also needs to bear in mind that "cold" PVD while not achieving a nanolaminated atomic structure would create an almost amorphous bonding network.…”
mentioning
confidence: 99%